Legal Protection for Foreign Workers in Indonesian Companies - Edi Hermawan , Haryono (The International Journal of Law Review and State Administration, 2024)
This study aims to understand the labor regulations for foreign workers in Indonesia. It employs a descriptive qualitative approach, using data collection techniques such as field surveys, direct observation of field conditions, and in-depth interviews with key respondents to gather accurate facts. The use of foreign workers in Indonesia remains relatively high and is challenging to avoid due to several factors, including the need for capital investment for development, the ongoing process of technology transfer, and limitations in local labor that meets required qualifications. Additionally, the use of advanced technology requiring skilled experts and the increasing demand from businesses that rely on foreign labor are key reasons. Indonesia has established legal regulations concerning foreign workers, including legal protections related to compensation fees for foreign labor and legal sanctions for employers who do not pay these fees. This normative legal research is conducted through the examination of theories, principles, regulations, and concepts. Thus, legal protection for foreign workers in Indonesia mandates that employers pay compensation fees for employing foreign workers, with administrative sanctions imposed on employers who fail to fulfill this obligation.